The art and sciences of Tuina: From past to present - Aree, Teera; Kritpet, Thananomwong; Pongkanpai, Ben (Health Science, Science and Technology Reviews, 2025)
Recently, alternative medicine was interested in its sciences, one of alternative therapy using the concept of patient center, and it was also holistic care. Chinese Tuina Massage has been one of the sciences on traditional Chinese medicine since the ancient era. The explicit knowledge of Chinese Tuina Massage has been developed continually has been around for a very long time, as evidenced by the scriptures “Huangdi Neijing”, the first traditional Chinese medicine textbook completely edited in Qin and Han Dynasty. Chinese Tuina Massage has been used to heal the disease in Ayurveda, Obstetrics & Gynecology, Pediatrics, Orthopedics etc. Additionally, there were investigations to apply Tui Na massage used in other areas of medicine including textbook of Chinese Tuina Massage was edited as considering the new information generated by treating various illnesses. The advantages were safety and disappearing of any side effects. Currently, Tuina is a popular alternative treatment as it restores balance to the body. It helps regulate the circulatory, nervous and muscular systems, relieves pain and promotes general health. It is also recognized by the World Health Organization for its effectiveness in treating disease. This article aims to provide a comprehensive analysis of the knowledge surrounding Tuina. Five key areas are covered: its history and development, underlying principles and practices, relevant theoretical frameworks, preparation for massage, and fundamental Tuina techniques. The discussion highlights the historical context, the theoretical foundations, and the systematic application of Tuina therapy in clinical practice.